Understanding sexual harassment: evidence-based forensic practice - Foote, William E. 19XX- (American Psychological Association, 2021)
"The much-anticipated revision of Evaluating Sexual Harassment: Psychological, Social, and Legal Considerations in Forensic Examinations. This completely updated second edition provides essential information to psychologists conducting evidence-based forensic consultation and other professionals who deal with sexual harassment cases in the era of #MeToo. Skillfully integrating relevant research with current case law, the book presents a method for comprehensively evaluating sexual harassment claims. Authors William E. Foote and Jane Goodman-Delahunty acquaint readers with clinical and social scientific literature on sexual harassment and apply it to issues that psychologists must consider in preparing ethically sound and well-substantiated forensic reports and testimony. The second edition is a valuable resource for all professionals working with sexual harassment cases, including psychologists, psychiatrists, lawyers, judges, and human resource professionals. Experienced forensic professionals will learn about the newest developments and most recent research in their field, while novice evaluators are provided with a tested framework fully grounded in research and sound practice. The book will help human resources professionals understand how people's reactions in the workplace may result in harassment, and legal professionals will benefit from the summary of research on the scientific and factual bases for forensic evaluation of sexual harassment plaintiffs"--